A holistic approach to understand helium enrichment in interplanetary coronal mass ejections: new insights. Issue 1 (27th April 2022) - , Yogesh; Chakrabarty, D; Srivastava, N
ABSTRACT: Despite helium abundance ( A He  = n H / n He ) being ∼8 per cent at the solar photospheric/chromospheric heights, A He can be found to exceed 8 per cent in interplanetary coronal mass ejections (ICMEs) on many occasions. Although various factors like interplanetary shocks, chromospheric evaporation, and 'sludge removal' have been separately invoked in the past to address the A He enhancements in ICMEs, none of these processes could explain the variability of A He in ICMEs comprehensively. Based on an extensive analysis of 275 ICME events, we show that there is a solar activity variation of ICME averaged A He values. We also found that the first ionization potential effect and localized coronal heating due to magnetic reconnection are not the major contributing factors for A He enhancements in ICMEs. Investigation on concurrent solar flares and ICME events for 63 cases reveals that chromospheric evaporation in tandem with gravitational settling determines the A He enhancements and variabilities beyond 8 per cent in ICMEs. While chromospheric evaporation releases the helium from chromosphere into the corona, the gravitationally settled helium is thrown out during the ICMEs. We show that the intensity and timing of the preceding flares from the same active region from where the CME erupts are important factors to understand the A He enhancements in ICMEs.